2014
DOI: 10.1097/mbc.0000000000000148
|View full text |Cite
|
Sign up to set email alerts
|

A simple method to identify patients on long-term warfarin who may derive the most benefit from new oral anticoagulants

Abstract: In many countries, new oral anticoagulants are only covered for patients with suboptimal anticoagulation control on vitamin K antagonists (VKAs). The quality of VKA management is often reported using the time in therapeutic range (TTR). We sought to predict a TTR 65% or less using a surrogate measure [number of changes in VKA dose and number of international normalized ratio (INR) tests] that could be easily determined by primary care physicians. This cross-sectional study included consecutive patients whose V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…This is similar to findings by Singer et al who correlated TTRs of around 66% to an average INR testing frequency of 19‐21 days. In contrast, Carrier et al associated poor control (TTR<65%) with a median of 12 tests over a six‐month period or a testing interval of 15 days. In addition, Schaefer et al identified poor control to be associated with long intervals between measurements but defined this as >14 days.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This is similar to findings by Singer et al who correlated TTRs of around 66% to an average INR testing frequency of 19‐21 days. In contrast, Carrier et al associated poor control (TTR<65%) with a median of 12 tests over a six‐month period or a testing interval of 15 days. In addition, Schaefer et al identified poor control to be associated with long intervals between measurements but defined this as >14 days.…”
Section: Discussionmentioning
confidence: 94%
“…Tight control of INR between 2.0 and 3.0 is the strategy used to ensure optimal benefit of warfarin while minimising risk . Time in therapeutic range (TTR) is a routinely used measure of warfarin control in clinical settings, with patients obtaining lower TTR more likely to experience negative outcomes such as haemorrhage or stroke . A minimum threshold TTR of 65% is recommended, but wide variations of TTR have been demonstrated by different countries and clinical settings …”
Section: Introductionmentioning
confidence: 99%
“…Poor control of TTR <65% was suggested by Carrier et al 29 to be associated with a median of 12 tests over a 6-month period (equating to a testing interval of 15 days). In contrast, we report lower mean TTR with increased frequency of testing; in particular, a frequency of less than 7 days was associated with a TTR of 63.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Poor control of TTR <65% was suggested by Carrier et al . to be associated with a median of 12 tests over a 6‐month period (equating to a testing interval of 15 days).…”
Section: Discussionmentioning
confidence: 99%
“…The testing interval of 17 days in Australia and 29 days in Singapore was similar to results from Oh et al(30) who reported a median interval of testing of 14 days in other world regions compared to 28 days in Asia. Carrier et al(31) concluded that patients with 9 or more INR tests and 3 or more dose changes in a six month period were more likely to have a TTR<65%. In contrast, our Australian population with an average of 10 tests and a mean 2.5 dose changes in the six month study had a high TTR of 82%.…”
mentioning
confidence: 99%